Understanding the Beauty of Movement and Meaning Behind Aceh Dance (Saman Dance) - Hulfadila, Hulfadila (Journal of Studies on Art, Culture and Society, 2025)
Saman Dance, a cultural heritage from Aceh that has been recognized by UNESCO as an Intangible Cultural Heritage, is a unique manifestation of local wisdom and Islamic values inherent in the Gayo community. This article examines the beauty of the movements and the deep meanings contained in Saman Dance, as well as its role in preserving Aceh's cultural identity. Through an ethnographic approach and semiotic analysis, this research explores the historical origins, choreographic structure, and symbolism of Saman Dance movements. The results show that every movement in Saman Dance has a philosophical meaning that is closely related to the teachings of Islam and the social values of Gayo society. The speed, uniformity, and complexity of the movements not only reflect aesthetic beauty, but also symbolize unity, discipline, and harmony in social life. Furthermore, the lyrics sung during performances contain profound moral and spiritual messages. This article also discusses the evolution of Saman Dance from a religious ritual to an internationally recognized performing art, as well as the challenges in preserving it in the modern era. In conclusion, Saman Dance is not just an artistic expression, but an important medium in transmitting cultural and spiritual values between generations. A deeper understanding of the meaning behind Saman Dance is expected to increase appreciation and efforts to preserve this cultural heritage.